DRIVER a spol., aneb spojení repozitáře se světem - Vyčítalová, Lucie (My University, 2011)
The presentation focuses on the repository connection to the world services which can enhance its visibility. Standards, metadata specifications, requirements are also mentioned.
Keywords: institucionální repozitáře; interoperabilita; DRIVER; OpenAIRE; statistiky; institucional repositories; interoperability; statistics